Determinants of Dietary Quality Intake among Adolescent Girls in Indonesia: The Role of Parental Education, Media Exposure, and Pocket Money - Gurdani Yogisutanti; Lilik Hidayanti; Fahmi Fuadah (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2026)
Background of study: high prevalence of undernutrition and high prevalence of overnutrition are particularly prevalent among adolescent girls in Indonesia. This study aims to identify factors associated with the dietary quality of adolescent girls in Tasikmalaya City. Methods: a cross-sectional design was used, involving 366 junior high school female students aged 13–15 years. Independent variables included parental occupation and education, family income, family size and type, physical activity, screen time, and pocket money. Data were collected using questionnaires, food recall forms, the Physical Activity Questionnaire (PAQ), stadiometers, and digital weighing scales. Data analysis included univariate (frequency), bivariate (Chi-Square test), and multivariate (logistic regression) methods. Data on respondent characteristics were collected and analyzed. Result: the majority of parents, both mother and father, had low education levels (77.9%, and 78.8% respectively). Most mothers were non-working (74.0%), while nearly all fathers were employed (98.1%). Over 50% of families had incomes below the minimum wage. Family size was mostly large, with 51.1% in larger families. Most respondents lived in nuclear families (91.5%). Physical activity was mostly in low category (95.4%), screen time was high in the category (88.3%), and pocket money was relatively low (69.1%). Most respondents had poor dietary quality intake (90.7%). Chi-Square analysis indicated significant associations between dietary quality and father’s education, screen time, and pocket money. Logistic regression confirmed that these factors collectively influenced dietary quality. Conclusion: These findings highlight the need for interventions targeting parental education, media exposure, and financial resources to improve adolescent dietary habits.